MANAJEMEN PEMBELAJARAN PROGRAM AKSELERASI DALAM PERSPEKTIF PENDIDIKAN ISLAM DI SMP NEGERI 2 KOTA SOLOK - Gusfitri Gusfitri (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Learning Management Acceleration Program in the Perspective of Islamic Educationin Junior High School 2 Solok. The problem in this study is that the gifted child education if notgiven in accordance with its characteristics, allowing for their inappropriate behavior as often out ofthe classroom, picking teacher in learning, like teasing and love searching for attention, easily bored,annoyed and indifferent in learning. In fact, many of them school dropouts are gifted, but because itdoes not obtain appropriate educational experience, they can be an underachiever. To overcome thiscondition, SMP Negeri 2 Solok held Acceleration Program.This study aims to describe the learning management accelerated program , and how the view ofIslamic education on an accelerated program at SMP Negeri 2 Solok Kata Kunci: Manajemen pembelajaran, program akselerasi